(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: Describe the current status of compliance with hypertension treatment and identify some related factors of patients receiving outpatient treatment at Nghe An General Friendship Hospital in 2023. Subjects and research methods: Horizontal cut representation. The study subjects were hypertensive people undergoing outpatient treatment for more than 1 month at Nghe An Friendship General Hospital. Results: After studying 250 hypertensive patients receiving outpatient treatment at A-Geriatric Clinic, Medical Examination Department during the period from February to September 2023, we found that 82.4% of patients achieved treatment compliance, 17.6% did not meet treatment compliance. 70.8% of research participants regularly took medication on time; 57.2% of young people occasionally forget to take antihypertensive medication. Education level, knowledge about hypertension and economic conditions are correlated with adherence to hypertension treatment. Conclusion: Research results show that patient compliance with treatment is at a regular level. Most patients do not pay attention to reducing salt intake, monitoring and controlling weight, and measuring blood pressure at home. And the following factors are correlated with treatment adherence with statistical significance p < 0.05: Education level, knowledge about hypertension and economic conditions of the patient. Among them, knowledge about the disease and the patient’s finances have the strongest correlation.